1949
DOI: 10.1086/625629
|View full text |Cite
|
Sign up to set email alerts
|

Structural Petrology of Planes of Liquid Inclusions

Abstract: Signature of Chairman of Department Committee on Graduate Students..... ,4-.. 9 fold-axis. Some evidence was found indicating that the planes may develop in the tensional direction. Quartz, then, may fail by shear or tensional rupture and in certain oases by deformation which produces lamellae that may be a type of translation-gliding. Failure by rupture along crystallographic directions has been described by one investigator, and has been produced experimentally in the laboratory. These different phenomena ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

1961
1961
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(39 citation statements)
references
References 7 publications
2
36
0
1
Order By: Relevance
“…(Hicks, 1884;Van Hise, 1890) appear as rectilinear succession of secondary fluid inclusions (Roedder, 1962(Roedder, , 1984. Tuttle (1949), Wise (1964), and more recently Lespinasse and P6cher (1986), Kowallis et al (1987), Laubach (1989), andRen et al (1989) have emphasised the use of FIT for relating the different stages of fluid percolation to a regional succession of deformational events. By studying microthermometric properties of the fluids trapped in the trails, P6cher et al (1985) have correlated the nature of the percolating fluid to specific directions of microfissuring and stress orientation.…”
Section: Methodsmentioning
confidence: 99%
“…(Hicks, 1884;Van Hise, 1890) appear as rectilinear succession of secondary fluid inclusions (Roedder, 1962(Roedder, , 1984. Tuttle (1949), Wise (1964), and more recently Lespinasse and P6cher (1986), Kowallis et al (1987), Laubach (1989), andRen et al (1989) have emphasised the use of FIT for relating the different stages of fluid percolation to a regional succession of deformational events. By studying microthermometric properties of the fluids trapped in the trails, P6cher et al (1985) have correlated the nature of the percolating fluid to specific directions of microfissuring and stress orientation.…”
Section: Methodsmentioning
confidence: 99%
“…Post-magmatic recrystallization and superimposition of many generations of secondary inclusions appears to be the rule rather than the exception (Tuttle, 1949;Alderton, 1983 andP6cher et al, 1985). Recent studies by London (1985) on the apparently coeval quartz and spodumene from the Tanco pegmatite have further shown that, even if well-formed primary inclusions are present, the results from the two minerals may be incompatible due to preferential subsolidus recrystallization of quartz.…”
Section: Significance Of Thermometric Data From Secondary Fluid Inclumentioning
confidence: 97%
“…Type V: Subgrain boundary and grain boundary fractures. Type VI: Fluid inclusion planes (always intragranular); these are shown as linear traces of bubbles, marking the location of healed (or sealed) fractures (e.g., TUTTLE, 1949).…”
Section: Microscale Damage Characteristicsmentioning
confidence: 99%